Degradation of porstaglandin F2alpha in the human pulmonary circulation. Issue 6 (December 1976) - Jose, P; Niederhauser, U; Piper, P J; Robinson, C; Smith, A P
Abstract : Degradation of prostaglandins (PGs) during passage through the human pulmonary circulation was investigated by measuring the transpulmonary plasma PGF2 alpha difference during continuous intravenous infusion of PGF2 alpha (5-10 mug/min). Seven patients with cardiological disorders and two patients with extensive pulmonary abnormalities were investigated during diagnostic cardiac catheterization. PGF2 alpha levels were measured by radioimmunoassay. The seven cardiac patients were found to have transpulmonary PGF2 alpha differences of 47-88%, indicating metabolism of the PG in the lungs. A patient with extensive bronchiectasis had an apparently normal transpulmonary PGF2alpha difference despite gross abnormalities in routine lung function tests. A patient with primary pulmonary arterial hypertension showed no metabolism of PGF2alpha in the pulmonary circulation. The results show that PG degradation is an aspect of normal lung function and suggest that it becomes imparied when extensive pulmonary vascular damage exists.